Integrating microdata for policy needs: The ESCB experience - Antonio Perrella; Julia Catz (European Central Bank (ECB), 2020)
Since the financial crisis, central bank policymakers have expressed a need for more integrated microdata for monetary policy purposes and for macroprudential and microprudential supervision, with a stronger focus on lending. In response to this policy need, the European System of Central Banks (ESCB) has increased the scope and quality of instrument-level data (e.g. loan-by-loan) it collects. At the same time, the ESCB has further developed the Register of Institutions and Affiliates Data (RIAD), which is pivotal in ensuring the successful linking of the databases, because it ensures the unique identification of counterparties. RIAD allows data to be aggregated using various types of company information, such as industrial activity or geographical location, but it also offers the possibility of aggregating data according to multiple group structures based on different concepts of what a "group" is. This paper discusses why there is a policy need for microdata and highlights some of the practical uses of the interlinked data. It also sheds more light on how information contained in different granular databases can be combined and aggregated in a flexible manner according to different business needs. It describes in detail the process of linking through a common stable identifier, points out current limitations and suggests a possible way forward.
Keywords: C81; E44; G32; 330; microeconomic data; granular data; unique identification; group structures; macroprudential; microprudential